2003
DOI: 10.1097/01.ccm.0000045547.12683.63
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia after hip arthroplasty may be related to a translocational rather than to a dilutional mechanism

Abstract: Hyponatremia after hip arthroplasty may not be related to a positive EFW balance. The postoperative increase of the OG(p) and the greater postoperative OG(u) in patients developing postoperative hyponatremia suggest the release of osmotically active solutes leading to cellular water shift from intracellular to extracellular spaces. These data may support the clinical relevance of the sick cell syndrome in the postoperative context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
0
8
0
2
Order By: Relevance
“…Other factors contributing to the development of hyponatraemia in hospitalised patients include the syndrome of inappropriate antidiuretic hormone secretion (SIADH), thiazide diuretics, selective serotonin reuptake inhibitor antidepressants, hypotonic intravenous fluids and surgery [4,13]. Post-operatively, the release of intracellular osmotically active solutes leading to cellular water shift into extracellular spaces (sick cell syndrome) has also been implicated [16,17]. Delirium and cerebral oedema have been noted in acute hyponatraemia and osmotic demyelination syndrome can occur after rapid correction of chronic hyponatraemia [1].…”
Section: Discussionmentioning
confidence: 99%
“…Other factors contributing to the development of hyponatraemia in hospitalised patients include the syndrome of inappropriate antidiuretic hormone secretion (SIADH), thiazide diuretics, selective serotonin reuptake inhibitor antidepressants, hypotonic intravenous fluids and surgery [4,13]. Post-operatively, the release of intracellular osmotically active solutes leading to cellular water shift into extracellular spaces (sick cell syndrome) has also been implicated [16,17]. Delirium and cerebral oedema have been noted in acute hyponatraemia and osmotic demyelination syndrome can occur after rapid correction of chronic hyponatraemia [1].…”
Section: Discussionmentioning
confidence: 99%
“…It was replaced by the current surgical and critical care paradigm: large quantities of salt and water are necessary postoperatively to prevent shock and preserve end‐organ function. Much attention has been focused on the prevention of postoperative hyponatraemia (12–24), often by emphasising the role of salt‐rich fluid postoperatively, although experimental work suggests that sodium administration may not prevent the phenomenon (14,22). Recently, several groups have observed that salt and water administration, even in the quantities recommended by many texts, appears to increase the risk of postoperative complications in colorectal patients (1–3), probably due to tissue oedema and hypoxaemia.…”
Section: Discussionmentioning
confidence: 99%
“…13 Mekanisme lainnya adalah cerebral salt wasting (CSW), hiponatremia translokasional, dan sick cell syndrome. 8,17,18 Risiko terjadinya hiponatremia pasca-operasi serta potensi bahaya yang ditimbulkan belum banyak disadari oleh para dokter yang bekerja di ruang perawatan intensif sehingga peneliti merasa bahwa penelitian mengenai hiponatremia pada pasien anak pasca-operasi perlu dilakukan.…”
Section: Hiponatremia Pada Anak Pasca Tindakan Operasi : Etiologi Danunclassified
“…Sick cell syndrome merupakan kondisi yang dikaitkan dengan sakit kritis sehingga kejadian hiponatremia akibat SCS diperkirakan akan lebih banyak terjadi pada jam-jam awal pasca-operasi. 18 Sedangkan pada SHATT kondisi hiponatremia sangat berhubungan dengan peningkatan sekresi HAD, yang mencapai puncak pada 12 jam setelah operasi dan masih dapat bertahan hingga 3-5 hari. 5,11,12,27 Penyebab adanya perbedaan etiopatogenesis hiponatremia pada penelitian ini dengan beberapa penelitian lain, yang menunjukkan SHATT sebagai etiologi tersering, belum dapat diketahui.…”
Section: Pembahasanunclassified